Strategies of Developing General Competencies of Pre-service Teachers of Music - Lasauskienė, Jolanta (Pedagogika, 2013)
According to the Lithuanian and foreign experience of educationalists, the present article discusses possibilities of developing general competencies of pre-service teachers of music by applying the project method. The research is related to analysis of opportunities to improve students’ competencies of reflection and learning to learn, as well as communication and cooperation. The problem of the research formulated: in what way and what impact project activities can exert on general competencies of future teachers of music; what are the basic strategies for developing general competencies of students involved in music pedagogy. The purpose of the research is to highlight basic strategies of developing general competencies of pre - service teachers of music. The methods of the research are as follows: analysis of scientific literature and documents, educational project, written student reflections, qualitative content analysis. Conclusions: The most important strategies connected with future music teacher general competencies by means of musical activity are related to the following: 1) promotion of students’ independent involvement in musical project activities (by strengthening the practice of socially important musical activities); 2) strengthening of teacher - student cooperation; 3) encouragement of learners to reflect and self - assess their own activities. Application of strategies related to development of general competencies during the educational project helped to fi various features connected with development of the competencies discussed above. It can be stated that the application of foreseen education strategies in project activities could have influenced the development of general competencies of future music teachers. While improving the study programmes for future music teachers, it is important to pay more attention to reflective teaching (learning) strategies and methods. While organizing project activities, it is advised to use the partnership based principles of pedagogy, which are validated on esteem, confidence and cooperation. While enhancing the independent student‘s involvement into musical project activities, it is advised to give the alternatives for students of activity selection.